2021
DOI: 10.3390/ani11020495
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Morphology and Glycan Composition of Mucins in Farmed Guinea Fowl (Numida meleagris) Intestine by the Multi-Strain Probiotic Slab51®

Abstract: Probiotics have become highly recognized as supplements for poultry.Since gut health can be considered synonymous withanimal health, the effects of probiotic Slab51® on the morphology and the glycan composition of guineafowlintestine were examined. The probiotics were added in drinking water (2 × 1011 UFC/L) throughout the grow-out cycle.Birds were individually weighed andslaughtered after four months. Samples from the duodenum, ileum and caecum were collected and processed for morphological, morphometric, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Villus height and crypt depth represent an indirect indication of the maturity and functional capacity of enterocytes; the longer the villi and crypts are, the greater number of enterocytes are present [92]. It is well known that crypt lengthening is mediated by a spectrum of local, immune, and neuro-humoral factors, as well as by diet composition [88,93,94]. It has been reported that CD is directly representative of the intestinal environment and may be used as an indicator of intestinal health [95].…”
Section: Histology Of the Small Intestinementioning
confidence: 99%
“…Villus height and crypt depth represent an indirect indication of the maturity and functional capacity of enterocytes; the longer the villi and crypts are, the greater number of enterocytes are present [92]. It is well known that crypt lengthening is mediated by a spectrum of local, immune, and neuro-humoral factors, as well as by diet composition [88,93,94]. It has been reported that CD is directly representative of the intestinal environment and may be used as an indicator of intestinal health [95].…”
Section: Histology Of the Small Intestinementioning
confidence: 99%